Cardiac Exposure in the Dynamic Conformal Arc Therapy, Intensity-Modulated Radiotherapy and Volumetric Modulated Arc Therapy of Lung Cancer. - Xin Ming; Yuanming Feng; Huan Liu; Ying Zhang; Li Zhou; Jun Deng (PLoS ONE, 2015)
Purpose To retrospectively evaluate the cardiac exposure in three cohorts of lung cancer patients treated with dynamic conformal arc therapy (DCAT), intensity-modulated radiotherapy (IMRT), or volumetric modulated arc therapy (VMAT) at our institution in the past seven years. Methods and materials A total of 140 lung cancer patients were included in this institutional review board approved study: 25 treated with DCAT, 70 with IMRT and 45 with VMAT. All plans were generated in a same commercial treatment planning system and have been clinically accepted and delivered. The dose distribution to the heart and the effects of tumor laterality, the irradiated heart volume and the beam-to-heart distance on the cardiac exposure were investigated. Results The mean dose to the heart among all 140 plans was 4.5 Gy. Specifically, the heart received on average 2.3, 5.2 and 4.6 Gy in the DCAT, IMRT and VMAT plans, respectively. The mean heart doses for the left and right lung tumors were 4.1 and 4.8 Gy, respectively. No patients died with evidence of cardiac disease. Three patients (2%) with preexisting cardiac condition developed cardiac disease after treatment. Furthermore, the cardiac exposure was found to increase linearly with the irradiated heart volume while decreasing exponentially with the beam-to-heart distance. Conclusions Compared to old technologies for lung cancer treatment, modern radiotherapy treatment modalities demonstrated better heart sparing. But the heart dose in lung cancer radiotherapy is still higher than that in the radiotherapy of breast cancer and Hodgkin's disease where cardiac complications have been extensively studied. With strong correlations of mean heart dose with beam-to-heart distance and irradiated heart volume, cautions should be exercised to avoid long-term cardiac toxicity in the lung cancer patients undergoing radiotherapy.